Governing Risks of Multi-Use: Seaweed Aquaculture at Offshore Wind Farms - van den Burg, Sander W. K.; Röckmann, Christine; Banach, Jennifer L.; van Hoof, Luc (Frontiers in Marine Science, 2020)
Spatial claims concerning the rapidly growing European offshore wind sector give rise to various ideas for the multi-use application of wind farms. Seaweed is considered a promising feedstock for food and feed that could be produced at offshore wind farms. Concerns about risks resulting in liability claims and insurance premiums are often seen as show-stoppers to multi-use at offshore wind farms. In this study, key environmental risks of seaweed cultivation at offshore wind farms, identified through literature review, are characterized based on stakeholder consultation. The current approach to risk governance is evaluated to assess how it can handle the uncertain, complex, and/or ambiguous risks of multi-use. It is concluded that current risk governance for multi-use is poorly equipped to deal with the systemic nature of risks. Risk governance should be a joint effort of governments and private regulators. It can improve if it is based on an adaptive framework for risk assessment that can deal with complex, systemic risks. Furthermore, it should be flexible and inclusive, i.e., open to new incoming information and stakeholder input, and taking into account and communicate about the different stakes and values of the various parties involved. The importance of communication and inclusion must be recognized, which promotes participation of concerned stakeholders.